Which standards from which disciplines? A test of systematic review for designing interdisciplinary evaluations. Issue 1 (2nd January 2017) - Delaney, Aogán; Tamás, Peter A.; Tobi, Hilde
ABSTRACT: Evidence-based development suggests empirical choice of evaluation methods. Systematic review (SR) is increasingly used in development but, to our knowledge, has not informed methods selection. This article tests SR for methods selection for evaluation in health and conflict studies. The review comprised a reproducible literature search, inclusion protocols, quality assessment, data extraction and qualitative aggregation. The study finds that adopting even some aspects of SR for methods selection to be useful and an improvement. The usefulness of SR is constrained by the paucity of empirically grounded methodological recommendations, inconsistent citation and reporting practices and difficulties surrounding multidisciplinary quality assessments.